2022
DOI: 10.1111/myc.13546
|View full text |Cite
|
Sign up to set email alerts
|

Perturbations of immune landscape in COVID‐19 associated mucormycosis

Abstract: Background: A rise in secondary fungal infections during the COVID-19 pandemic necessitates a deeper understanding of the associated immunological perturbations. Objectives: To evaluate the clinical and immunological characteristics observed in patients with COVID-19 associated mucormycosis (CAM) infection. Patients/ Methods: Cases of mucormycosis with or post-COVID-19 infection were compared with cases of acute COVID-19 and convalescent COVID-19. Lymphocyte subsets, cytokines and other laboratory markers were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…If any spores survive and germinate, then hyphae trigger neutrophils chemotaxis, which kills the germinated spores through the production of pro-inflammatory cytokines, such as tumor necrosis factor-α, interferon (IFN)-γ, and interleukin (IL)-1β, and reactive oxygen metabolites, cationic peptides, perforin which attracts and activate other immune cells. [18] Due to the strong binding of platelets to mucorale spores and hyphae, they also contribute to the host's immune response during infection. As soon as the platelets bind to the pathogen and get activated, they start to destroy the hyphae by secreting the granular pro-and anti-inflammatory cytokines and chemokines having antifungal properties.…”
Section: Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…If any spores survive and germinate, then hyphae trigger neutrophils chemotaxis, which kills the germinated spores through the production of pro-inflammatory cytokines, such as tumor necrosis factor-α, interferon (IFN)-γ, and interleukin (IL)-1β, and reactive oxygen metabolites, cationic peptides, perforin which attracts and activate other immune cells. [18] Due to the strong binding of platelets to mucorale spores and hyphae, they also contribute to the host's immune response during infection. As soon as the platelets bind to the pathogen and get activated, they start to destroy the hyphae by secreting the granular pro-and anti-inflammatory cytokines and chemokines having antifungal properties.…”
Section: Pathogenesismentioning
confidence: 99%
“…If any spores survive and germinate, then hyphae trigger neutrophils chemotaxis, which kills the germinated spores through the production of pro‐inflammatory cytokines, such as tumor necrosis factor‐α, interferon (IFN)‐γ, and interleukin (IL)‐1β, and reactive oxygen metabolites, cationic peptides, perforin which attracts and activate other immune cells. [ 18 ]…”
Section: Pathogenesismentioning
confidence: 99%
“…The immunological status of patients who develop pulmonary mucormycosis post SARS‐CoV‐2 infection is unclear 6,8 . Few studies from India highlighted the clinical and immunological characteristics observed among CAPM patients 9,10 . In a pan‐India case–control study, several previously known host factors, such as organ transplantation, diabetes mellitus and immunosuppression, were implicated in CAPM 11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…6,8 Few studies from India highlighted the clinical and immunological characteristics observed among CAPM patients. 9,10 In a pan-India case-control study, several previously known host factors, such as organ transplantation, diabetes mellitus and immunosuppression, were implicated in CAPM. 11,12 The treatment regime for COVID-19 patients (with glucocorticoids and zinc supplementation) was also identified as a risk factor, significantly associated with CAPM.…”
Section: Introductionmentioning
confidence: 99%